PENGARUH BUDAYA ORGANISASI DAN KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PT. KINGKATA KHARISMA ARTHA - Yenny Yenny; Alfonsius Alfonsius; Syawaluddin Syawaluddin (JURNAL BISNIS KOLEGA, 2019)
Abstract. This study examines "The Effect of Organizational Culture and Leadership on Employee Performance of PT. Kingkata Kharisma Artha Medan." Researchers assess that a decrease in employee performance can be caused by a lack of motivation and cooperation between employees. This may be due to organizational culture and leadership that are not good at implementation. Therefore, the authors are interested in analyzing and knowing more about the influence of organizational culture and leadership on employee performance in this company. This research was conducted at PT. Kingkata Kharisma Artha Medan with a total sample of 52 people. The sampling technique used is saturated samples and data collection techniques using documentation studies, interviews, observations and questionnaires that have been shared. While for data analysis, researchers used validity and reliability tests, classic assumption tests, multiple linear regression analysis, coefficient of determination and hypothesis testing. The conclusion of this study is that organizational culture and leadership do not affect the performance of employees of PT. Kingkata Kharisma Artha Medan. This is because the value of R Square is 0.007 which means that organizational culture and leadership can explain employee performance by 0.7% and the remaining 99.3% is influenced by other variables outside of this study such as: compensation, personality and so on.Â Keywords : Organizational Culture, Leadership, Performance